Experimentation in Markets - Dirk Bergemann; Juuso Valimaki (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1996)
We present a model of entry and exit with Bayesian learning and price competition. The value of the new product is initially unknown in the market, but purchases of the product yield information on its true value. We assume that the performance of the new product is publicly observable. As agents learn from the experiments of others, informational externalities arise. We determine the Markov Perfect Equilibrium prices and allocations in different market structures. In a single market, the informational externality among the buyers leads to too much learning. If the entry of the new product occurs in many distinct markets, then efficiency is reestablished in the limit as the number of markets grows. We finally analyze entry into different market segments and show that the new firm starts by selling to the informationally inexpensive buyers.
Keywords: 330